Disk-Less Network Implementation using Cyberindo Program (Case: BAHONET2 Siantar Game Center) - Tama Rudia Naibaho; Sumarno Sumarno; Zulaini Masruro Nasution; Indra Gunawan; Bahrudi Efendi Damanik (IJISTECH (International Journal of Information System and Technology), 2019)
The hard disk device used on the personal computer (pc) client at the game center, however, must have decreased durability because it is used continuously as in the BAHONET2 Siantar game center. This problem can be overcome with various solutions, but the authors prefer the diskless network method using the Cyberindo program as a solution to the problem. The author begins to design the diskless network in question, which is a windows-based application that is used to run, configure, and perform diskless processes through the server. Before the design is done, the authors identify problems that arise in the system that was previously used. This is done in order to avoid various errors on the old system in system implementation so that the results obtained are more optimal. After being implemented, the authors conclude that the diskless system using the Cyberindo program can reduce the use of local hard disks and also faster client performance, the client can be operated properly like using a local hard disk. Also there is no need to update the game manually on each client, we only need to update the game on the server so that all clients can automatically play the updated game.